2021
DOI: 10.1177/13621688211014538
|View full text |Cite
|
Sign up to set email alerts
|

Teacher enthusiasm and students’ social-behavioral learning engagement: The mediating role of student enjoyment and boredom in Chinese EFL classes

Abstract: Teacher enthusiasm is attracting growing attention in educational and learner psychology research. There is evidence that teacher enthusiasm is contagious in class and positively affects student emotions. Their fundamental role in shaping student engagement has also been well documented. However, the links – between teacher enthusiasm and student emotions, and between student emotions and engagement – remain underexplored in instructed second language acquisition. The present study adopted a mixed-method appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
141
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(157 citation statements)
references
References 71 publications
12
141
1
3
Order By: Relevance
“…Research studies on FLE have focused on its conceptualization, measurement, antecedents, and correlates in the language learning process (e.g., Li et al, 2018;Jin and Zhang, 2019). Reviewing the existing literature indicated that FLE can lead to better academic achievement (Jin and Zhang, 2018;Li et al, 2020), L2 motivation (MacIntyre, 2016), and social-behavioral learning engagement (Dewaele and Li, 2021).…”
Section: Positive Psychology Factors Enjoymentmentioning
confidence: 99%
See 1 more Smart Citation
“…Research studies on FLE have focused on its conceptualization, measurement, antecedents, and correlates in the language learning process (e.g., Li et al, 2018;Jin and Zhang, 2019). Reviewing the existing literature indicated that FLE can lead to better academic achievement (Jin and Zhang, 2018;Li et al, 2020), L2 motivation (MacIntyre, 2016), and social-behavioral learning engagement (Dewaele and Li, 2021).…”
Section: Positive Psychology Factors Enjoymentmentioning
confidence: 99%
“…But, it needs to be mentioned that in comparison with the domain of educational research, language learning is at its infancy, having just initiated to study L2 engagement in connection with learning different languages in different contexts and cultures (Hiver et al, 2020a). Within the extant literature, students' L2 engagement was found to be positively related to teacher care, rapport (Derakhshan et al, 2021a), nonverbal immediacy, and credibility behaviors (Derakhshan, 2021), emotions, grit (Khajavy, 2021), enjoyment (Dewaele and Li, 2021), willingness to communicate (Mystkowska-Wiertelak, 2021), and bilingual/biliteracy learning (Zhang et al, 2012).…”
Section: Academic Engagementmentioning
confidence: 99%
“…Students in the poor reading proficiency group tended to report lower values, suggesting that they were more likely to perceive their reading teachers as having low enthusiasm in the classroom. Research suggests that teacher enthusiasm is indirectly related to student achievement in language classes, with teacher enthusiasm directly influencing students' learning engagement in the classroom [49].…”
Section: Teacher-related/instructional Variablesmentioning
confidence: 99%
“…In this way, classroom enjoyment can be supposed as the preference practiced when students admire learning the subject matter (constructive review) and feel proficient in managing and finalizing the tasks they are confronted with (control). Accordingly, enjoyment is thought to be of the greatest prominence for the following feeling of fulfillment, which matches educational accomplishment (Ainley and Hidi, 2013;Piechurska-Kuciel, 2017;Dewaele and Li, 2021). Considering enjoyment as a multidimensional paradigm, it holds five mechanisms including the emotional, intellectual, motivational, communicative, and physical (Hagenauer and Hascher, 2014;Elahi Shirvan and Taherian, 2020), in which attention has been drawn mainly to the first three.…”
Section: Enjoymentmentioning
confidence: 99%